Future exacerbations and mortality rates among patients experiencing COPD exacerbations: a meta-analysis of results from the EXACOS/AVOIDEX programme - Jennifer K Quint; Hana Müllerova; Clementine Nordon; Deven Patel; Juan José Soler-Cataluña; Giovanni Sotgiu; Jonathan Marshall; Kirsty Rhodes; Claus F Vogelmeier; Barry J Make; John Haughney; Pierachille Santus; et al. (BMJ Open)
Objectives Exacerbations of chronic obstructive pulmonary disease (COPD) can lead to reduced lung function and worse clinical outcomes. Previous studies have reported associations between severe exacerbations and increased risk of hospitalisation and/or mortality. This meta-analysis examined the impact of moderate exacerbations on the risk of future exacerbations and all-cause mortality.Design This meta-analysis included seven observational studies from the EXACOS (EXAcerbations of COPD and their OutcomeS)/AVOIDEX (Impact of AVOIDing EXacerbations of COPD) programme studies.Data sources This meta-analysis used data from regional claims databases or electronic healthcare records from seven countries.Eligibility criteria The individual studies included patients with a diagnosis of COPD and ≥12 months of data availability before (regarded as baseline) and after the index (ie, the date of the first COPD diagnosis), with postindex data considered the follow-up period.Data extraction and synthesis The number of COPD exacerbations experienced during the baseline period (ie, the exposure variable) was used to categorise patients into the following groups: no exacerbations, one moderate exacerbation only or two or more moderate/severe exacerbations. Outcomes assessed included risk of COPD exacerbations and all-cause mortality during follow-up as a function of baseline exacerbations. For meta-analyses, all rate ratios (RRs) were log-transformed, and associations were pooled across studies using random-effects meta-analysis models.Results Among 2 733 162 patients with COPD, one moderate exacerbation was significantly associated with a twofold increased risk of future exacerbations compared with having no exacerbations during baseline, with pooled RRs (95% CIs) of 2.47 (1.47 to 4.14) at 1 year, 2.49 (1.38 to 4.49) at 2 years and 2.38 (1.30 to 4.34) at 3 years postindex. The pooled RR (95% CI) for all-cause mortality was 1.30 (1.05 to 1.62), indicating a 30% increase in risk following one moderate exacerbation versus no exacerbations.Conclusions Preventing moderate exacerbations in patients with COPD should be a priority that may improve patient trajectories and outcomes.